THE METHOD OF SEQUENTIAL LINEARIZATION IN PROBLEMS OF OPTIMIZING THE INTENSITY OF MAINTENANCE DEVICES OF MULTIPHASE SYSTEMS OF MASS SERVICE - R. Z. Khayrullin; A. S. Kornev (Современная наука и инновации)
The adaptation of the method of sequential linearization is described. The mathematical model of service center technical maintenance of measuring equipment is developed. The results of solving the problem of optimal redistribution of production capacity are presented